A Lean Six Sigma framework for the insurance industry: insights and lessons learned from a case study - Kai Sandner; Sebastian Sieber; Marleen Tellermann; Frank Walthes (Journal of Business Economics, 2020)
It has long been recognized in the literature that the Lean and Six Sigma methodologies can complement each other fruitfully. So far, however, researchers have not been able to derive definitive conclusions on how to combine these methods; furthermore, there is little research on how to apply them to service firms. We develop a framework for integrating Lean and Six Sigma instruments in the service industry, particularly in the insurance sector, and discuss it in the context of the insights we gained from a large-scale project carried out at a large German insurance company. We show how various instruments drawn from these two methodologies can be (a) adapted to the insurance industry and (b) combined productively to enable a company to achieve its strategy and goals. The conclusions we draw from these insights can help a wide range of companies customize the combination of the Lean and Six Sigma approaches to suit their specific needs.
Keywords: G22; L89; M11; M54; 650; Insurance industry; Lean; Process improvement; Six Sigma